(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The problem of environmental taxation is relevant to Ukraine and the world, and more and more scientists are paying attention to its research. Economic instruments should be used to obtain a sustainable result in terms of improving the ecological situation in Ukraine. Such an instrument is environmental taxes and benefits. The article substantiates the urgency of the ecological problem at the global and local scale, and environmental taxation is one of the most powerful levers of its solution. Foreign countries use environmental taxes to stimulate investment and innovation activities in the field of environmental protection. It is important to note that the feature of ecological taxation is that environmental progress is achieved with the least losses for the economy compared with other regulatory instruments. The use of price incentives by taxation of «harmful production» by higher taxes in comparison with «environmentally friendly» alternatives has a more flexible reaction of producers and consumers. Taxes stimulate behavior change through a system of stimulation, rather than coercion. It is obvious that the ecological taxation system in Ukraine is in its initial phase. At the same time, an important role is played by the level of environmental consciousness of the population and business in the country, since the question of environmental taxation is not exclusively economic or legal, and above all, is moral and ethical, and every positive changes in this direction are possible only with the understanding of the importance of it by every citizen .